The Ecological Component of Tourism Development in the Region - RAKHMETULLINA, Shynar Zhakanovna; TRUSHEVA, Sharafat; SAVANCHIYEVA, Armanay Sagatbayevna; YESSIMOVA, Dinara; ARYNOVA, Zulfiya Amangeldinovna (Journal of Environmental Management and Tourism; Vol 8 No 2 (2017): JEMT Volume VIII Issue 2(18) Spring 2017DO - 10.14505//jemt.v8.2(18).14, 2017)
The article considers the existing economic mechanisms of environmental management in the Republic of Kazakhstan. The study showed that the natural and climatic resources of the country are favorable for the development of the travel industry in the region. However, the ecological situation in the Pavlodar Region represents one of the major threats in development of tourism, including eco-tourism. Creation of eco-tourism infrastructure in the Pavlodar Region may become an additional source of income of the regional budget and one of the promising trends of economic advancement of the region. The author comes to the conclusion that the current tax system is not conducive to the sustainable use of natural resources for the purposes of tourism.